N-Desmethyldauricine Induces Autophagic Cell Death in Apoptosis-Defective Cells via Ca2+ Mobilization - Law, Betty Y. K.; Mok, Simon W. F.; Chen, Juan; Michelangeli, Francesco; Jiang, Zhi-Hong; Han, Yu; Qu, Yuan Q.; Qiu, Alena C. L.; Xu, Su-Wei; Xue, Wei-Wei; Yao, Xiao-Jun; Gao, Jia Y.; et al. (Frontiers in Pharmacology, 2017)
Resistance of cancer cells to chemotherapy remains a significant problem in oncology. Mechanisms regulating programmed cell death, including apoptosis, autophagy or necrosis, in the treatment of cancers have been extensively investigated over the last few decades. Autophagy is now emerging as an important pathway in regulating cell death or survival in cancer therapy. Recent studies demonstrated variety of natural small-molecules could induce autophagic cell death in apoptosis-resistant cancer cells, therefore, discovery of novel autophagic enhancers from natural products could be a promising strategy for treatment of chemotherapy-resistant cancer. By computational virtual docking analysis, biochemical assays, and advanced live-cell imaging techniques, we have identified N-desmethyldauricine (LP-4), isolated from rhizoma of Menispermum dauricum DC as a novel inducer of autophagy. LP-4 was shown to induce autophagy via the Ulk-1-PERK and Ca2+/Calmodulin-dependent protein kinase kinase β (CaMKKβ)-AMPK-mTOR signaling cascades, via mobilizing calcium release through inhibition of SERCA, and importantly, lead to autophagic cell death in a panel of cancer cells, apoptosis-defective and apoptosis-resistant cells. Taken together, this study provides detailed insights into the cytotoxic mechanism of a novel autophagic compound that targeting the apoptosis resistant cancer cells, and new implication on drug discovery from natural products for drug resistant cancer therapy.